Ten questions concerning energy flexibility in buildings. (September 2022) - Li, Rongling; Satchwell, Andrew J.; Finn, Donal; Christensen, Toke Haunstrup; Kummert, Michaël; Le Dréau, Jérôme; Lopes, Rui Amaral; Madsen, Henrik; Salom, Jaume; Henze, Gregor; Wittchen, Kim
Abstract: Demand side energy flexibility is increasingly being viewed as an essential enabler for the swift transition to a low-carbon energy system that displaces conventional fossil fuels with renewable energy sources while maintaining, if not improving, the operation of the energy system. Building energy flexibility may address several challenges facing energy systems and electricity consumers as society transitions to a low-carbon energy system characterized by distributed and intermittent energy resources. For example, by changing the timing and amount of building energy consumption through advanced building technologies, electricity demand and supply balance can be improved to enable greater integration of variable renewable energy. Although the benefits of utilizing energy flexibility from the built environment are generally recognized, solutions that reflect diversity in building stocks, customer behavior, and market rules and regulations need to be developed for successful implementation. In this paper, we pose and answer ten questions covering technological, social, commercial, and regulatory aspects to enable the utilization of energy flexibility of buildings in practice. In particular, we provide a critical overview of techniques and methods for quantifying and harnessing energy flexibility. We discuss the concepts of resilience and multi-carrier energy systems and their relation to energy flexibility. We argue the importance of balancing stakeholder engagement and technology deployment. Finally, we highlight the crucial roles of standardization, regulation, and policy in advancing the deployment of energy flexible buildings. Highlights: Energy flexibility characterization methodologies are needed at the aggregated level. There is a trend toward decentralized and distributed architectures to harness energy flexibility. Buildings with/within multicarrier energy systems offer higher levels of flexibility. Multidisciplinary approaches are needed to address various aspects of the topic. Supportive policies are key to enable opportunities and incentivize stakeholders.